2014
DOI: 10.3844/ajidsp.2014.105.117
|View full text |Cite
|
Sign up to set email alerts
|

LIQUID AND VAPOUR PHASE ANTIBACTERIAL ACTIVITY OF <i>EUCALYPTUS GLOBULUS</i> ESSENTIAL OIL = SUSCEPTIBILITY OF SELECTED RESPIRATORY TRACT PATHOGENS

Abstract: Essential Oils (EO) produced by medicinal plants have been traditionally used for respiratory tract infections and are used nowadays as ethical medicines for colds. Although several studies of Eucalyptus Globulus Labill. Essential Oil (EGEO) have been reported, there are no reports describing vapour activity of EGEO against bacterial respiratory tract pathogens. The aim of this study was to test the efficacy of the Algerian EGEO against some respiratory tract pathogens by disc diffusion and vapour diffusion me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…It is suggested that lipophilic molecules in the EOs’ aqueous phase associate, form micelles, and restrain the attachment of EOs to microorganisms. The vapour phase is devoid of this disadvantage that allows antimicrobials to be easily released and to strongly attach to microbial structures [ 30 ]. Due to the aforementioned volatility and water immiscibility of EOs, evaluation of their antimicrobial activity using in vitro assays displays certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that lipophilic molecules in the EOs’ aqueous phase associate, form micelles, and restrain the attachment of EOs to microorganisms. The vapour phase is devoid of this disadvantage that allows antimicrobials to be easily released and to strongly attach to microbial structures [ 30 ]. Due to the aforementioned volatility and water immiscibility of EOs, evaluation of their antimicrobial activity using in vitro assays displays certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The growing published evidence towards a more effective antimicrobial activity of EOs in vapor phase compared to EOs in liquid form applied by direct contact [45][46][47] led to identification of new applications for EOs vapors, including those in the food industry [46,47]. One plausible explanation for the different antimicrobial effectiveness is the mechanism presented by the group of researchers Nadjib et al [48] indicating formation of micelles from association of lipophilic molecules in the aqueous phase which negatively interfere with the EOs attachment to the microorganisms, while the EO vapors allow free attachment to microorganism's cells.…”
Section: Antimicrobial Effect Of Pfunctionalizing the Wpc-efmentioning
confidence: 99%
“…Indeed, the vapour generated by essential oils has a more significant antimicrobial effect than that of direct contact with these oils in liquid form. Lipophilic molecules in the aqueous phase could associate and form micelles which limit the fixation of EOs to microorganisms [ 95 ]. According to Kloucek et al, there is variability in the phenomenon of essential oils’ volatility.…”
Section: Resultsmentioning
confidence: 99%